KEBANGKITAN EKONOMI USAHA MIKRO KECIL DAN MENENGAH: Diskusi Dan Solusi Bersama Radio Republik Indonesia - Purwanto Setiyo; Wuryandari Nur Endah Retno (STIE PGRI Dewantara Jombang, 2024)
Through a talk show broadcast on RRI PRO 1 FM, this Community Service Program (PkM) aims to encourage Micro, Small and Medium Enterprises (MSMEs) to work together and exchange ideas to produce solutions and innovations that support the revival of the national economy. This activity utilizes a talk show involving MSME players. The talk show focused on solutions and innovations that can support the growth of MSMEs and their role in driving the revival of the national economy. Results of PkM Implementation and its Implications: By working together with MSME players as a companion in sharing experiences, solutions, and innovations that can make a positive contribution to the national economy, we managed to make a contribution. This activity resulted in a stronger collaboration network between MSME players, an increase in their insights and knowledge, and an increased awareness of the role of MSMEs in supporting national economic circulation.